A new species of Basilia Miranda-Ribeiro (Diptera: Nycteribiidae) from Honduras, parasite of Bauerus dubiaquercus (Van Gelder) (Chiroptera: Vespertilionidae: Antrozoinae) - Graciolli, Gustavo; Dick, Carl W. (Zootaxa, 2009)
Basilia (Basilia) dubiaquercus sp. nov. (Diptera: Nycteribiidae) is described. The new species was collected from the bat Bauerus dubiaquercus (Van Gelder) (Chiroptera: Vespertilionidae) in Honduras. The habitus, abdomen, and male terminalia are figured. Placement of the new species among established species groups of Basilia (Basilia), as well as the conservation status of the species, is discussed.